Pengaruh Penggunaan Digital Payment Terhadap Kinerja UMKM di Kota Makassar - Zaldy, Zaldy. M; Arman, Andi; Darwin, Khadijah (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to determine the effect of digital payment usage on the performance of MSMEs in Makassar City. The method used was quantitative with a simple linear regression technique on 99 MSME respondents. The analysis results show that digital payment usage has a positive and significant effect on MSME performance, with a calculated t-value of 9.646 > t-table 1.984 and a significance level of 0.000 < 0.05. The R-square value of 0.490 indicates that 49% of the variation in MSME performance is explained by the use of digital payments. This study concludes that digital payments play a significant role in improving MSME performance. It is recommended that MSMEs utilize these services more actively and that the government support them through digital training.